Implementation of Mixed Care Practices in Child Welfare Services Networks in Public State Social Institutions: Pelaksanaan Amalan Penjagaan Campuran dalam Jaringan Perkhidmatan Kebajikan Kanak-kanak di Institusi Sosial Awam Negara - Abdul Rauf, Siti Hajar; Abu Bakar Ah, Siti Hajar; Abd Wahab, Haris (Journal of Techno-Social, 2020)
This article discuss about an effort to map out local child welfare network, in particular, the public institutional social care. The objective of the study is to explore the child welfare network practices implementation. The study which is qualitative in its approach utilised Grounded Theory to gather the data. A series of face-to-face and in-depth interviews have been done among 30 respondents that come from 24 different agencies. The finding show that the operations of the child welfare network system in Malaysia is in conflict with the mixed economy of care approach. The Social Network Development Model was developed to respond to the empirical evidence. This model can be instrumental in developing an integrated child welfare network in Malaysia.